Application of hydrogel polymers and fertilizers for increasing winter wheat grain yield in conditions of rain-fed agriculture - Sahakyan, Samvel; Avagyan, Gayane; Yedoyan, Tatevik; Daveyan, Sevak; Eloyan, Arevik (Edelweiss Applied Science and Technology, 2024)
This study aims to address the critical issue of water scarcity, which is being intensified by climate change and presents significant challenges to rain-fed agriculture, especially in arid regions. The research focuses on enhancing winter wheat grain yield productivity under rain-fed conditions through the utilization of locally produced, environmentally friendly hydrogel polymers. The methodology involved a field experiment conducted in the Spitak community, Armenia, from 2022 to 2023, covering an area of 630 m². Along with control groups, the study had 21 experimental treatments that used Aquasource and Van polymers in different ways, with and without nitrogen, phosphorus, and potassium (NPK) fertilizer. The findings indicated that the application of Aquasource and Van polymers at doses of 50-100 kg ha⁻¹ and 750-1000 kg ha⁻¹, respectively, without fertilizers significantly increased soil moisture absorption during the tillering and heading stages by 11.5-12.5% and 5.5-7.5%, compared to the controls. On the other hand, using these polymers with NPK fertilizer (N50P50K50 and N100P100K100) together made it harder for plants to absorb water, especially when more polymers were used. Soil moisture levels had a substantial impact on winter wheat grain yield metrics during these growth stages, demonstrating a strong correlation (R = 0.71-0.91). Enhanced moisture absorption resulting from polymer application led to a 22-24% increase in winter wheat grain yield. The practical implications of this study lie in its identification of key factors that influence winter wheat yield in rain-fed agriculture, particularly regarding locally sourced polymer dosage and application methods, both independently and in conjunction with fertilizers.